2017
DOI: 10.3389/fphar.2017.00546
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of the Quality of Ciprofloxacin and Antibiotic Resistance in Developing Countries

Abstract: Ciprofloxacin, a second generation broad spectrum fluoroquinolone, is active against both Gram-positive and Gram-negative bacteria. Ciprofloxacin has a high oral bioavailability and a large volume of distribution. It is used for the treatment of a wide range of infections including urinary tract infections caused by susceptible bacteria. However, the availability and use of substandard and spurious quality of oral ciprofloxacin formulations in the developing countries has been thought to have contributed towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 57 publications
0
46
1
1
Order By: Relevance
“…Recent studies have reported that 20–40 percent of anti-malarials and antibiotics sold in official outlets in Ghana fail quality standards (<= 80% of active ingredient: Kaur et al, 2016; Fadeyi et al, 2015; Tivura et al, 2016). Globally, poor-quality anti-malarial and antibiotic medicines are thought to be responsible for more than 100,000 under-five deaths annually, concentrated in Sub-Saharan Africa (Renschler et al, 2015; WHO, 2017b), in addition to risks of accelerated antimicrobial resistance that arise through persistent under-dosing (Dondorp et al, 2009; Newton et al, 2016; Brock et al, 2018; Sharma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that 20–40 percent of anti-malarials and antibiotics sold in official outlets in Ghana fail quality standards (<= 80% of active ingredient: Kaur et al, 2016; Fadeyi et al, 2015; Tivura et al, 2016). Globally, poor-quality anti-malarial and antibiotic medicines are thought to be responsible for more than 100,000 under-five deaths annually, concentrated in Sub-Saharan Africa (Renschler et al, 2015; WHO, 2017b), in addition to risks of accelerated antimicrobial resistance that arise through persistent under-dosing (Dondorp et al, 2009; Newton et al, 2016; Brock et al, 2018; Sharma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…All N,O-acetal derivatives showed good predictions for absorption values in the human intestine, similar to atovaquone, ciprofloxacin, and furazolidone. Indeed, the compounds 7b and 7c showed absorption values greater than 90%, close to that of ciprofloxacin, which is a good estimative for oral bioavailability 29 .…”
Section: Discussionmentioning
confidence: 65%
“…9 This widespread distribution of poor quality cipro, and the linkage to resistant bacteria, is in part due to a lack of regulatory policies governing appropriate manufacturing and quality assurance. 2 Many methods are used to assess the quality of cipro formulations, including the 'gold-standard' high performance liquid chromatography (HPLC) and the 'field-standard' thin-layer chromatography (TLC). 7 -9 Currently, HPLC is the main analysis method for pharmaceutical formulations but is prohibitively expensive for applications in low-resource settings, costing upwards of US$ 100,000 with reoccurring annual costs of approximately US$ 20,000.…”
Section: Conclusion Onclusionsmentioning
confidence: 99%